Influence of Gd3+ on structural and luminescence properties of new Eu3+-doped borate glass for photonics material. (June 2023) - Wantana, N.; Kaewnuam, E.; Chanlek, N.; Kim, H.J.; Kaewkhao, J.
Abstract: The Gd2 O3 –La2 O3 –ZnO–B2 O3 –Eu2 O3 glasses with different Gd2 O3 concentration (Gd:LaZnBEu) were studied in the physical, structural, optical and luminescence properties. The density and refractive index of glass increased with addition of Gd2 O3 content. The FTIR spectra demonstrated the BO3 and BO4 borate complexes as the main construction in glass those were more disturbed by Gd2 O3 increasing. The BO4 /BO3 and bridging/non-bridging oxygen ratio, observed from XPS, changed by following the Gd2 O3 concentration whose 10 mol% owned the highest values of both ratios. In the absorption spectra, glasses absorbed some photons in UV – NIR region. The excitation by O 2− →Eu 3+ charge transfer (240 nm), Gd 3+ →Eu 3+ energy transfer (275 nm) and direct Eu 3+ excitation (394 nm) caused the strongest Eu 3+ photoluminescence at 613 nm ( 5 D0 → 7 F2 ). The glass with 5 mol%-Gd2 O3, that possessed the optimum Eu 3+ local site, exhibited the highest absorbance and photo-/radio-luminescence intensity. The CIE 1931 and UV lamp excitation revealed the strong reddish-orange emission of glasses. The photoluminescence decay time of Eu 3+ in glasses were between 1.6 and 2.1 ms and decreased with added Gd2 O3 amount. The Gd:LaZnBEu glasses have a potential for LED, laser, display, and X-ray detection devices with integration mode. Highlights: The strong luminescence of Eu 3+ under different excitations on Eu 3+, Gd 3+ and charge transfer. High absorbance and luminescence intensity by the optimum BO4 /BO3 and BOs/NBOs ratio in glass. The strong reddish-orange emission for LED, laser, display and X-ray detection applications.